IMPLEMENTATION OF BIOLOGY LEARNING BASED ON LOCAL SCIENCE CULTURE TO IMPROVEMENT OF SENIOR HIGH SCHOOL STUDENTS LEARNING OUTCOME IN CIREBON DISTRICT AND KUNINGAN DISTRICT - Kartimi Kartimi (Scientiae Educatia: Jurnal Pendidikan Sains, 2014)
The purposes of this research are to assess : 1) Application of biology learning based on local science culture in Cirebon district and Kuningan district, 2) Improvement of students learning outcome which apply biology learning based on local science culture in Cirebon district and Kuningan district, 3) The difference of students learning outcome which apply biology learning based on local science culture in Cirebon district and Kuningan district, 4) Students’ respond to application of biology learning based on local science culture in Cirebon district and Kuningan district.          This research uses quantitative approach with experimental methods, and the research design called by one group pretest-postest design. Population of 10th grade senior high school students is 1055 persons, 129 persons are picked as the sample. Sample is chosen by Cluster random sampling technique. Written test and questionnaire are used as the instruments. Two way annova statistical research is used as data analysis techniques.          The results of the study showed the average improvement of Students Learning outcome which apply biology learning based on local science culture in Kuningan district is higher than Cirebon district. Based on a Two Way Anova test, significance values obtained 0.04 <0.05. There are significant differences between the improvement students’ learning outcome which apply biology learning based on local science culture in Cirebon district and Kuningan district. Biology learning based on local science culture gets positive responses from the students.